2023
DOI: 10.1002/adfm.202306340
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine PtMo Nanocrystals Confined on N‐Doped Carbon Toward Efficient pH‐Universal Hydrogen Evolution Reaction

Abstract: Pt‐based nanocrystals with tunable electronic structure and optimized atom efficiency are essential for boosting the hydrogen evolution reaction (HER) performance and further industrial application. However, the synthesis of uniform and ordered nanocrystals is still a challenge due to the uncontrollable size growth of metal particles, restricting the active sites toward the desired catalytic activity. Herein, the synthesis of ultrafine bimetal PtMo nanocrystals on N‐doped carbon (PtMo‐NC) through an anchoring‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…04-0802). [40][41][42] Although there is no obvious diffraction peak associated with Pt in the XRD pattern of Pt-Ni(OH) 2 @Ni-CNFs-2, the lattice fringe of the surface nanoparticle with a spacing of 0.224 nm in the high-resolution (HRTEM) image ascribes to the (111) plane of metallic Pt (Fig. 2d).…”
Section: Fabrication and Characterization Of Catalystsmentioning
confidence: 99%
“…04-0802). [40][41][42] Although there is no obvious diffraction peak associated with Pt in the XRD pattern of Pt-Ni(OH) 2 @Ni-CNFs-2, the lattice fringe of the surface nanoparticle with a spacing of 0.224 nm in the high-resolution (HRTEM) image ascribes to the (111) plane of metallic Pt (Fig. 2d).…”
Section: Fabrication and Characterization Of Catalystsmentioning
confidence: 99%
“…21 The adsorption energy of hydroxyl ions (OH*) plays a crucial role in determining the dissociation rate of water, and subsequently, the production of H* intermediates, which are essential for enhancing alkaline and neutral HER activity. 22,23 To attain the perfect equilibrium between H* adsorption and desorption on MoC, it is common to introduce electron-rich transition metals (such as Fe, Co, Ni), which exhibit suitable binding energies for OH*, making for water dissociation and active intermediate adsorption to enhance electrocatalytic activity. 24 Moreover, non-metallic element doping (such as P, N) can also improve the electronic structure of electrically active molybdenum carbide and reduce the energy barrier in the pH-universal HER process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, transition metal compounds, including carbides, nitrides, sulfides, oxides, phosphides, selenides, etc ., have received much attention for their excellent electrochemical properties. 15–28 In particular, nickel-based selenides available at a low price have shown excellent electrocatalytic performance in alkaline electrolytes due to the production of active species (oxy)hydroxides during the OER. 29–32 Wu et al reported an efficient bimetallic Ni–Fe selenide-derived OER electrocatalyst (Ni–Fe–Se nanocages) and presented a novel concept that the local ligand structure distortion and disorder of the active sites contribute to a significantly improved OER behavior.…”
Section: Introductionmentioning
confidence: 99%